Comparing Personal Protective Equipment Practice among Health Worker's Job Role and Hospital Unit - Perdani, Fandaruzzahra Putri; Chalidyanto, Djazuly (Jurnal Kedokteran Brawijaya, 2022)
Health workers have the highest risk exposure that can increase the pathogen infection risk during the Covid-19 pandemic. The use of Personal Protective Equipment (PPE) is the most significant prevention, but mistakes while using PPE may occur in the donning (putting on) and doffing (taking off) process. This study compares the practice of using PPE among groups of health providers and hospital service units. The study design was a cross-sectional study conducted on non-infectious hospital employees in one specific hospital in Surabaya, totaling 102 employees. The Infection Prevention and Control Link Nurse (IPCLN) of the hospital conducted observations and analyses of health personnel in inpatient and triage units, treatment units, and support units. Based on the job roles, the employees were divided into health providers, healthcare support workers, and other health workers. Work units were categorized into inpatient units, outpatient and triage units, treatment units, and support units (cashier and registration areas). The results of the assessment were measured using One-Way ANOVA. Based on the job role, significant errors occurred when removing masks (p=0.048) made by health workers (38%). Meanwhile, in the hospital unit category, significant errors occurred in removing masks (p=0.000) and the use of gloves (p=0.002). Most mistakes were made in the outpatient and triage units, 92% and 42%, respectively. The complexity of wearing and removing PPE requires increased awareness and updated training on the correct use of PPE for all health workers who work in hospitals based on WHO recommendations during the Covid-19 pandemic.